Nephrotic syndrome after treatment with d-penicillamine in a pediatric patient with Wilson's disease - M. Farallo; C. Amoruso; C. Frattini; G. Ardissino; G. Nebbia (PAGEPress Publications, 2012)
We describe a case of nephrotic syndrome (NS) after a 7 months treatment with D-penicillamine in a 14 years old girl with Wilson's disease , with a prompt regression at the discontinuation of the drug. Kidney function, proteinuria in particular, must be always monitored during the chelating therapy, and the drug must be discontinued as soon as signs of renal injury are detected.